Evolution of Forensic Nursing Theory——Introduction of the Constructed Theory of Forensic Nursing Care: A Middle-Range Theory. Issue 4 (October 2020) - Valentine, Julie L.; Sekula, L. Kathleen; Lynch, Virginia
Abstract : ABSTRACT: The constructed theory of forensic nursing care is a middle-range nursing theory developed from the integrated practice model for forensic nursing science, a conceptual framework. Theory evolution was achieved following a critique of the conceptual framework and through inductive and deductive reasoning. A review of nursing theory growth and significance of middle-range theories is presented as background information in understanding the importance of this emerging forensic nursing middle-range theory. The philosophical and theoretical foundations of forensic nursing are bolstered with the addition of three nursing theories, two healthcare models and one social theory. Links are made between theory components and the current state of forensic nursing. Assumptions and concepts are clearly defined. The middle-range theory provides three testable propositions to frame forensic nursing practice, education, and research. Research conducted on the propositions will expand the forensic nursing scientific base leading to enhanced evidence-based practice. A pictorial model illustrates the propositions as relational statements. The constructed theory of forensic nursing care affirms the focus of forensic nursing care is on the nurse–patient relationship and improved health outcomes. Additional results of forensic nursing care are improved forensic science and criminal justice system outcomes. Abstract : Supplemental digital content is available in the text.